Photoluminescence studies of Eu3+ doped Y2O3 nanophosphor prepared by microwave hydrothermal method - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Ravi, V.; Kakade, Bhalchandra A.; Saaminathan, V. (Applied Physics Letters, 2006)
In this letter, the authors report the photoluminescence studies of Eu3+ doped Y2O3 nanorods, which have been synthesized by rapid microwave hydrothermal route within 6 min. The nanostructured Eu3+ doped Y2O3 is characterized by x-ray diffraction, transmission electron microscopy, and photoluminescence. The emission spectrum shows transitions from the excited 5D(0) state to F-7(J) (J=0,1,2,3,4) levels of the Eu3+ ion. The most intense peak around 612 nm is due to the D-5(0)-> F-7(2) transition, expected from the Judd-Ofelt selection rules [B. R. Judd, Phys. Rev. 127, 750 (1962); G. S. Ofelt, J. Chem. Phys. 37, 511 (1962)]. Photoluminescence measurements demonstrated that the nanocrystalline Eu3+:Y2O3 phase shows higher photoluminescence intensity. (c) 2006 American Institute of Physics.